The angiotensin-converting enzyme insertion/deletion polymorphism and serum levels of angiotensin-converting enzyme in venous thromboembolism - Ay, Cihan; Bencur, Peter; Vormittag, Rainer; Sailer, Thomas; Jungbauer, Christof; Vukovich, Thomas; Mannhalter, Christine; Pabinger, Ingrid (Thrombosis and Haemostasis, 2007)
The angiotensin-converting enzyme (ACE) has been suggested to affect blood coagulation and fibrinolysis. Results from literature on the role of the frequent insertion/deletion (I/D) polymorphism in the ACE gene in venous thromboembolism (VTE) are controversial. Only limited data on ACE serum levels in VTE exist. We determined the ACE I/D polymorphism by genotyping and ACE serum levels by an enzymatic assay in 100 high-risk patients with objectively confirmed recurrent VTE and at least one event of an unprovoked deep venous thrombosis or pulmonary embolism. One hundred twenty-five age- and sex-matched healthy individuals served as controls. ACE genotype frequencies were not significantly different between patients (DD: 26.0%,ID: 52.0%, II: 22.0%) and controls (DD: 29.6%, ID: 44.8%, II: 25.6%; p=0.56). Neither individuals with ACE DD genotype nor those with ACE ID genotype had a higher risk for VTE in comparison to those with ACE II genotype (odds ratio and [95% confidence interval]: 1.0 [0.5–2.1] and 1.4 [0.7–2.6], respectively). Serum ACE levels (U/l) did not differ between patients (median = 25.25, 25th –75th percentile: 20.20–33.70) and controls (24.20, 17.85–34.50, p=0.49). In the total population involved in the study the ACE DD genotype (n=63: 36.00 [26.40–43.00]) was associated with higher ACE levels than the ACE ID genotype (n=108: 24.10 [19.80–31.48], p<0.001) and the ACE II genotype (n=54: 19.35 [15.00–22.95], p<0.001). In conclusion, we found a significant association of the ACE I/D polymorphism with ACE serum levels. However, neither the serum levels nor the I/D genotype were associated with VTE.
Keywords: Angiotensin-converting enzyme; insertion/deletion polymorphism; deep venous thrombosis; pulmonary embolism; venous thromboembolism